Sm2O3 nanoparticles preparation using caesalpinia pulcherrima leaf extract, characterization and photocatalytic activity. Issue 1 (July 2020) - Putri, N; Yulizar, Y; Umar, A; Apriandanu, D O B
Abstract: In this research, Sm2 O3 nanoparticles (NPs) have been prepared via Caesalpinia pulcherrima leaf extract (CPE), whichh contains secondary metabolites contained as a weak base source and a capping agent. The nanoparticles were confirmed by UV-Vis DRS, FT-IR spectroscopy, XRD, PSA and TEM. FT-IR spectrum showed that CPE contains the secondary metabolites which play an essential role in the preparation of Sm2 O3 NPs. UV-Vis DRS result showed that the bandgap value of Sm2 O3 NPs was approximately 4.76 eV which works in the UV region. Based on the XRD analysis, Sm2 O3 NPs have a structure of cubic. PSA characterization showed that the average particle size distribution of Sm2 O3 was around 84.47 nm. TEM image confirmed that Sm2 O3 was in nanoscale with the particle size of 73.27 nm. Finally, Sm2 O3 NPs have been tested for the photodegradation of malachite green (MG) under UV light illumination. The degradation percentage of MG using Sm2 O3 NPs photocatalyst was 80.14 % for 2 h.